Effect of a Universal Mindfulness Program on Well-Being in Adolescents: A Cluster Randomized Controlled Trial - Qvick, Jemina; Hintsanen, Mirka; Vahlberg, Tero; Volanen, Salla-Maarit (Springer Nature, 2026)
Mental health disorders often emerge during adolescence. Mindfulness interventions may support adolescents’ well-being. However, the evidence supporting the effectiveness of universal mindfulness interventions for adolescents’ well-being is limited and hampered by methodological weaknesses. The present study is the first large-scale randomized controlled trial with active and inactive control groups to examine the effectiveness of a 9-week universal mindfulness intervention on the well-being of adolescents, moderated by gender, age, and independent practice. A total of 3519 Finnish adolescents aged 12–15 were randomly assigned to intervention, active, and inactive control groups. Well-being was indicated by life satisfaction (assessed with OECD life satisfaction and SWLC-C life satisfaction) and positive and negative affect (assessed with PANAS) at baseline, 9 weeks, and 26 weeks. Analyses were conducted with linear mixed models. A significant increase in life satisfaction (SWLS-C) was observed at 9 weeks in the mindfulness intervention group (β = 0.38, 95% CI 0.08–0.68, p = 0.009) compared to the active control group. Independent practice was found to moderate the effects in positive affect at 26 weeks; those who practiced more had increases in positive affect. Universal mindfulness intervention shows some promise in improving the well-being of adolescents, although it did not affect all well-being outcomes.